Black males matter : a blueprint for creating school and classroom environments to support their academic and social development : a sourcebook - Dyce, Cherrel Miller; Davis, Julius; Gunn, Shadonna (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"A major premise of the book is that teachers, school leaders, and school support staff are not taught how to create school and classroom environments to support the academic and social success of Black male students. The purpose of this book is to help champion a paradigmatic shift in educating Black males. This books aims to provide an asset and solution-based framework that connects the educational system with community cultural wealth and educational outcomes. The text will be a sourcebook for in-service and pre-service teachers, administrators, district leaders, and school support staff to utilize in their quest to increase academic and social success for their Black male students. Adopting a strengths-based epistemological stance, this book will provide concerned constituencies with a framework from which to engage and produce success"-- Provided by publisher.
Keywords: African American boys -- Education.; School environment -- United States.; Classroom environment -- United States.; Community and school -- United States.; Education -- Administration -- General.; Educational administration and organization.; elektronické knihy; electronic books